Gidon Kremer: Finding Your Own Voice Portrait of a world-class violinist, from Paris to Riga and Moscow - Schubert, Franz; Pärt, Arvo; Pärt, Arvo; Pärt, Arvo; Desyatnikov, Leonid; Kissine, Victor; Weinberg, Mieczysław; Weinberg, Mieczysław; Glass, Philip; Pärt, Arvo (Accentus Music, 2018)
Don't miss the chance to learn more about violinist Gidon Kremer, one of the most fascinating artists of our time. He began studying the violin with his father--Jewish survivor of the Holocaust--and his grandfather before becoming one of the most prized students of David Oistrakh at the Tchaikovsky Conservatory in Moscow. Paul Smaczny followed Kremer all over the world: alongside his chamber orchestra Kremerata Baltica in Paris and his hometown of Riga, Latvia, and to a solo tour in Moscow and Tokyo. This elegant portrait casts a thoughtful light on the aspirations of a violinist and intellectual, in constant pursuit of the deeper meaning of things, of music, and of the world
Keywords: documentaries; Internet videos